Influence of behavior, personal ability and leadership on cooperative performance in Aceh Province, Indonesia - Rizal, Syamsul (International Journal of Scientific Research and Management (IJSRM), 2018)
This research was conducted to see the effect of behavior, personal ability and leadership on cooperative performance in Aceh Province. Data were obtained by distributing questionnaires to several respondents. Data processing follows multiple linear. The results showed that the behavior affects the performance of cooperatives, personal capabilities affect the performance of cooperatives, leadership affect the performance of cooperatives in Aceh Province.  Behavior, personal ability and leadership simultaneously affect the performance of cooperatives in Aceh Province.Keywords: behavior, personal ability and leadership, performance